G166 Usefullness of social emotional and adaptive behaviour as part of two year neurodevelopmental assessments. (12th March 2018) - Metheniti, D; Parmar, M; Southernwood, P; Beasley, S; Merchant, N
Abstract : Introduction: Neurodevelopmental outcome assessment provides basis for benchmarking and early intervention. Bayleys scale of infant development (BSID) is often used in 2 year assessments of high-risk infants, however there are time constraints in completing these assessments. Social, emotional and adaptive processes like self regulation and executive function which are increasingly being shown to predict later life and behaviour outcomes are often not captured in these assessments. Aim: To study if completion of social emotional and adaptive questionnaire of BSIDIII will be useful as part of the 2 year assessments. Methods: Social-emotional/adaptive parental questionnaire was given for all preterms born <30 weeks at the 2 year neurodevelopmental clinic. Demographic and infant data was collated along with the composite scores of the cognitive, language and motor, social emotional and adaptive scales of BSIDIII. Moderate delay was defined as composite score of 70–84 and severe delay as <70. Data was analysed using Microsoft Excel and STATA. Results: 19/48 (40%) who returned the questionnaire had 2 year assessments at a mean age of 25 months. Table 1 shows the mean composite scores of different scales. There was significant correlation with general adaptive composite (GAC) and motor composite (p=0.04, 95% CI −1.29 to −0.33). A significant correlation was also seen with language composite and social adaptive domain (p=0.042, 95% CI −0.7 and −0.15). There was no correlation seen with social emotional scale and motor/language/cognitive scales. Conclusion: Parental questionnaire using the social-emotional and adapative behaviour items can be used as screening tool to identify high-risk infants requiring speech and physiotherapy intervention. This may allow streamlining of clinics that run the 2 year assessments. This data needs to be validated with a larger cohort.